Determinan Perubahan Struktur Modal pada Usaha Mikro Kecil dan Menengah - Permana, Gusi Putu Lestara; Endita, Ni Kadek Citra; Dewi, Putu Purnama; P, Kadek Wulandari Laksmi (Jurnal Akuntansi Terapan dan Bisnis, 2024)
This study emphasizes the importance of broader access to financial services, the use of evolving financial technology, and financial literacy in capital structure decision-making for MSMEs. The study examined 75,620 SME units using the pecking order theory and resource-based view theory, selecting 75 responders using the Hair formula. The data analysis used SPSS software for classical assumption tests, multiple linear regression analysis, coefficient of determination tests, and partial t-tests. Results show that financial inclusion, technology, and literacy positively and significantly affect capital structure decisions. These three independent factors explain 53.8% of capital structure decisions. Thus, the pecking order theory and resource-based view theory help Gianyar Regency SMEs make capital structure decisions. The study emphasizes the importance of broader access to financial services, the use of emerging financial technology, and financial literacy in making capital structure decisions for MSMEs